2020
DOI: 10.1177/0954406220937734
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental thermal performance with entropy generation analysis on tube with helical screw tape inserts at number of strips in turbulent flow

Abstract: In the heat exchangers, twisted tape insert is a technique to enhance heat transfer. In this paper, the experimental and numerical investigations are arranged to analyze thermal performance with entropy generation analysis on single and double strip helical screw tape inserts. The finite volume method is used with shear stress transport K-ω model to analyze fluid flow in tube with inserts. The Nusselt number attained enhancement with double strip as compared to single strip helical screw inserts at de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…12, 14a and 15a is that the thermal entropy generation of TPT and TECT is less than that of the PT. This is owing to heat transfer improvement with TPT and TECT as compared to PT [54]. As can be discerned, the generation of thermal entropy decreases when vortex flow increases.…”
Section: The Local Entropy Generationmentioning
confidence: 91%
“…12, 14a and 15a is that the thermal entropy generation of TPT and TECT is less than that of the PT. This is owing to heat transfer improvement with TPT and TECT as compared to PT [54]. As can be discerned, the generation of thermal entropy decreases when vortex flow increases.…”
Section: The Local Entropy Generationmentioning
confidence: 91%
“…The main device used in the majority of thermal applications is a heat exchanger. [1][2][3] HT in the heat exchanger can be enhanced by the reduction in thermal resistance. This reduction can be achieved either by the generation of turbulence or by enhancing the effective HT area.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Heat pipes are being widely utilized as waste heat recovery equipment because they are highly efficient and do not cause pollution. 13,14 These pipes are similar to thermosiphons and it is useful to have adequate knowledge of their function. In this equipment, a small amount of water or other fluids are poured into the tubes, and then the air is discharged from the tube and sealed at its two ends.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical results revealed that the combination was able to enhance the cooling capacity by up to 68%. In one study, 13 a mathematical model 14 was developed to determine the air velocity, hot section temperature, and charging ratio. The results indicated a productive potential in the cooling part although different capacities were also detected in the thermoelectric coolers.…”
Section: Introductionmentioning
confidence: 99%